Europe road trip: the adventure / Nurul Najwa Yusoff ... [et al.] - Yusoff, Nurul Najwa; Hamdan, Nurul Najiha; Mohd Yunus, Nursyafiqah; Khalid, Nor Athierah; Daud, Shahreena (Universiti Teknologi MARA, Kedah, 2023)
Financial planning is exceptionally important, including for younger generations. There are various ways to manage personal finances. Europe Road Trip: The Adventure is one of the tools to help individuals enhance their knowledge and awareness in managing their personal finance. This board game is inspired by Monopoly but with a little bit of twist. Players will need their own spending and earning planning so that they can spend their road trip with joy. This board game is able to fix several problems including lack of financial budgeting and tracking, insufficient emergency fund, lack of discipline and impulse spending. Furthermore, multiple objectives of this board game are also mentioned which can provide the insight of what Europe Road Trip: The Adventure can help in managing funds and debts. Additionally, the uniqueness of this board game is that players will encounter various significant events which will test their decision making for their financial situation, and how they manage debt between the players and the banker. Moreover, with straightforward instructions, Europe Road Trip: The Adventure is easy to play and can be played anywhere at any time while motivating players to be more competitive and expand their knowledge about financial planning.